2016
DOI: 10.17058/reci.v6i2.6218
|View full text |Cite
|
Sign up to set email alerts
|

Acidentes de trabalho com exposição a material biológico: Descrição dos casos na Bahia

Abstract: Exceto onde especificado diferentemente, a matéria publicada neste periódico é licenciada sob forma de uma licença Creative Commons -Atribuição 4.0 Internacional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
21

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 10 publications
1
13
0
21
Order By: Relevance
“…One of the proposed measures to reduce biological risk is the use of PPE. The results of this research indicate that gloves were the PPE with the highest use record with 1,589 (75.5%) cases, which is similar to other investigations (15,21) . Although gloves do not prevent percutaneous accident, it acts as a mechanical barrier which is capable of reducing the amount of inoculated material by up to 75%.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…One of the proposed measures to reduce biological risk is the use of PPE. The results of this research indicate that gloves were the PPE with the highest use record with 1,589 (75.5%) cases, which is similar to other investigations (15,21) . Although gloves do not prevent percutaneous accident, it acts as a mechanical barrier which is capable of reducing the amount of inoculated material by up to 75%.…”
Section: Discussionsupporting
confidence: 88%
“…The nursing staff had the highest exposure to biological material (1,169, 55.5%) with indication for clinical and laboratory follow-up, which is similar to the findings of other studies (13)(14) . The high prevalence of accidents among these professionals is due to direct and uninterrupted patient care, frequent handling of sharps, multiple employment relationships and work overload (15)(16) .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported factors associated with the higher occurrence of occupational accidents among female nursing professionals with little professional experience and absence of PPE (24)(25) .…”
Section: Discussionmentioning
confidence: 99%
“…No mesmo estudo, 87,5% dos trabalhadores declararam terem sido vacinados, dos quais parcela menor (84,3%) recebeu esquema completo da vacina, dados semelhantes aos verificados nesta investigação, embora alguns estudos refiram que os percentuais de cobertura vacinal neste grupo de trabalhadores são variados conforme o país estudado e, no caso do Brasil, por regiões geográficas. [14][15][16][17][18][19] Após a identificação dos profissionais que declararam terem recebido as três doses de imunobiológico contra hepatite B, procedeu-se o convite e a coleta de material sanguíneo para realização de teste sorológico de contagem de anticorpos anti-HBs, com o intuito de se conhecer a prevalência de não soroconversão entre os vacinados.…”
Section: Agradecimentosunclassified